Reducing slag treatment material, concrete containing reducing slag treatment material and preparation method of reducing slag treatment material
By adjusting the components of the electric furnace reducing slag, high content of γC2S and magnesium silica stone materials were prepared, which solved the problems of high carbon dioxide emissions and high material costs in the existing technology, and achieved efficient carbon dioxide fixation and supported carbon medium. and the realization of society.
Patent Information
- Application Number
- CN202410837836.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-12
- Filing Date
- 2024-06-26
- Publication Date
- 2025-01-14
AI Technical Summary
The prior art has high carbon dioxide emission problems when producing γC2S and magnesium silite, and the material cost is high, making it difficult to produce in large quantities, and the carbon dioxide absorption is insufficient to emissions, resulting in positive carbon problems.
By adjusting the components, slowly cooling and grading the reduced slag of the electric furnace, a reducing slag treatment material with γC2S and/or magnesium silite as the main components with an average particle size of less than 0.6 mm is prepared, and is used to prepare a fixing capacity of high concentrations of carbon dioxide. concrete.
It has achieved effective preparation of high-content γC2S and magnesium silica stone materials without using fossil fuels, reducing carbon dioxide emissions, improving carbon dioxide fixation capacity, and supporting the realization of a carbon neutral society.
Smart Images

Figure CN119306419A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a reducing slag treated material, concrete containing the reducing slag treated material and a method for preparing the reducing slag treated material, and in particular to a reducing slag treated material with γC2S (γ-2CaO·SiO2) and / or magnesia calcium silicate (3CaO·MgO·2SiO2) as main components, concrete containing the reducing slag treated material and a method for preparing the reducing slag treated material. Background Art
[0002] Cement has been used extensively as a raw material for concrete, and since its production uses fossil fuels, it is a material that emits a large amount of carbon dioxide. Therefore, as part of measures to combat global warming, it is necessary to reduce carbon dioxide emissions when producing concrete.
[0003] During this process, someone proposed the following invention: using γC2S or magnesia calcium silicate that easily reacts with carbon dioxide as an admixture, kneading it with a small amount of water, cement and aggregate to form a concrete-like material, and hardening it by absorbing high concentrations of carbon dioxide, thereby fixing a large amount of carbon dioxide inside the cement-based material (concrete) (for example, refer to Patent Document 1).
[0004] Patent Document 1: Japanese Patent Application Publication No. 2011-168436
[0005] Non-patent literature 1: Ryosuke Yasuda et al., "Investigation of analytical methods for evaluating the carbon dioxide content in cement-based materials during carbonation", Cement Concrete Papers, Vol. 75, p. 442-447, 2021. Summary of the invention
[0006] In this way, γC2S and magnesia calcite can become key materials for building a carbon-neutral or negative carbon society.
[0007] On the other hand, when preparing γC2S, for example, limestone or silica is mixed, the composition is adjusted, and then calcined at 1200-1400°C. However, the material is expensive, so there is a problem that it is difficult to mass produce. The same is true for magnesia calcite.
[0008] In addition, when preparing γC2S or magnesium silicate, the decarbonization and oxidation treatment of limestone and the use of a large amount of fossil fuels are indispensable, which will cause the emission of carbon dioxide to be higher than the absorption (fixed amount) of carbon dioxide, and there will be a problem of positive carbon.
[0009] Therefore, a technology is needed that can effectively obtain a composition containing γC2S or magnesia calcite as a main component while not emitting carbon dioxide when preparing the composition.
[0010] However, there is a kind of electric furnace reduction slag, which is a material with a chemical composition similar to γC2S or magnesia calcite. Electric furnace reduction slag and electric furnace oxidation slag are produced in the refining process of recycling scrap iron as the main raw material in the ironmaking industry. At present, electric furnace reduction slag and electric furnace oxidation slag are mixed and used as a low-value-added civil engineering material.
[0011] Therefore, in the ironmaking industry and the steelmaking and rolling processing industry, it is necessary to effectively utilize the reduced slag discharged from the electric furnace, that is, to seek to switch to high value-added material applications.
[0012] The present invention is made in view of the above-mentioned problems, and an object of the present invention is to provide a reduced slag treated material containing a large amount of γC2S and / or magnesia silicea as main components, and concrete containing the reduced slag treated material.
[0013] In addition, another object of the present invention is to provide a method for preparing a reduced slag treated material, which method can use electric furnace reduced slag to prepare a composition containing a large amount of γC2S and / or magnesia calcium silicate as main components.
[0014] After intensive research, the inventors of the present invention found that the content of γC2S and / or magnesia-calcium siliceous stone in conventional electric furnace reduction slag discharged from an electric furnace is relatively low, but by obtaining a graded powder with a particle size distribution with an average particle size of less than 0.6 mm, a reduction slag treatment material with a higher content of γC2S and / or magnesia-calcium siliceous stone as the main component can be prepared than in the past.
[0015] Specifically, it was found that by adjusting the composition of electric furnace reduced slag under certain conditions, slowly cooling and classifying it, a reduced slag treated material containing a large amount of γC2S and / or magnesia calcium silicate can be effectively prepared.
[0016] In addition, it was discovered that if this preparation method is used, fossil fuels will not be used as in the past, and a cement-based material (concrete) that can fix carbon dioxide well can be achieved, which can realize a carbon-neutral (negative carbon) society, which led to the creation of the present invention.
[0017] Therefore, the above-mentioned problem is solved by the following method. According to the present invention, the reducing slag processing material is a reducing slag processing material with γC2S and / or magnesia calcium silicate (3CaO·MgO·2SiO2) as the main component, the reducing slag processing material has an average particle size of 0.6 mm or less, and has the following particle size distribution, when the reducing slag processing material is sieved using a JIS standard sieve (JIS Z8801-1:2000), more than 80% of the total weight of the reducing slag processing material can pass through the sieve with a mesh size of 0.6 mm.
[0018] At this time, it is preferred that when the chemical composition of the reducing slag treatment material totals 100 weight percent, the weight percent of CaO is 50-70%, the weight percent of SiO2 is 25-40%, the weight percent of MgO is 5-15%, and the particle size distribution has a sieve with a mesh size of 0.6 mm and more than 90% of the total weight of the reducing slag treatment material can pass through.
[0019] In addition, it is preferred that the reduced slag treated material has an average particle size of less than 0.3 mm and has the following particle size distribution, when the reduced slag treated material is sieved using a JIS standard sieve, more than 80% of the total weight of the reduced slag treated material can pass through a sieve with a mesh size of 0.3 mm.
[0020] In addition, it is preferred that when the chemical composition of the reducing slag-treated material totals 100 weight percent, the weight percent of CaO is 50-65%, the weight percent of SiO2 is 25-35%, the weight percent of MgO is 5-10%, and the chemical composition of the primary crystallization zone of C2S in the CaO-SiO2-Al2O3 (weight percent of MgO = 10%) ternary phase diagram has a particle size distribution in which more than 90% of the total weight of the reducing slag-treated material can pass through a sieve with a mesh size of 0.3 mm.
[0021] In addition, the above-mentioned problems are solved as follows: The concrete containing the reduced slag treated material according to the present invention contains the reduced slag treated material and fixes carbon dioxide.
[0022] In addition, the above-mentioned problem is solved as follows. The method for preparing a reduced slag treatment material according to the present invention is a method for preparing a reduced slag treatment material having γC2S (γ-2CaO·SiO2) and / or magnesia calcium silicate (3CaO·MgO·2SiO2) as main components using reduced slag discharged from an electric furnace, comprising a composition adjustment process, a slow cooling process and a classification process, wherein the composition adjustment process adjusts the composition of the reduced slag; the slow cooling process slowly cools the reduced slag after the composition adjustment; the classification process classifies the slowly cooled reduced slag to obtain a classified powder of the reduced slag; in the classification process, the classified powder is obtained, having an average particle size of less than 0.6 mm, and having the following particle size distribution, when sieved using a JIS standard sieve (JIS Z8801-1:2000), more than 80% of the total weight can pass through a sieve with a mesh size of 0.6 mm.
[0023] At this time, it is preferred that, in the composition adjustment process, the composition of the reducing slag is adjusted so that the composition of the primary crystallization zone is C2S in the ternary phase diagram of CaO-SiO2-Al2O3 (weight percentage of MgO = 10%), in the slow cooling process, the reducing slag after the composition adjustment is slowly cooled in a reducing atmosphere, and in the classification process, the classified powder is obtained, having an average particle size of less than 0.3 mm and the following particle size distribution, when sieved using a JIS standard sieve, more than 80% of the total weight can pass through a sieve with a mesh size of 0.3 mm.
[0024] According to the present invention, it is possible to realize a reduced slag-treated material containing a large amount of γC2S and / or magnesia-calcite as a main component, and concrete containing the reduced slag-treated material.
[0025] In addition, a method for preparing a reduced slag treated material can be realized, which can use electric furnace reduced slag to prepare a composition containing a large amount of γC2S and / or magnesia calcium silicate as the main component. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a ternary phase diagram of CaO-SiO2-Al2O3 (weight percentage of MgO = 10%).
[0027] Figure 2 This is a graph showing the particle size distribution results of the reduced slag treatment material.
[0028] Figure 3 It is a graph showing the chemical composition (%) of reduced slag-treated materials, γC2S and magnesia ferrocene with different average particle sizes.
[0029] Figure 4 This is a graph showing the results of evaluating the carbon dioxide fixation capacity (%) of reduced slag treated materials having different average particle sizes. DETAILED DESCRIPTION
[0030] Below, refer to Figure 1-Figure 4 Embodiments of the present invention will be described.
[0031] The present embodiment is an invention related to "reduced slag treated material", which is a treated material obtained by treating reduced slag discharged from an electric furnace, and contains more γC2S and / or magnesia calcium silicate (3CaO·MgO·2SiO2) as main components compared to the past.
[0032] In addition, the present invention relates to "concrete containing a reduced slag treated material" and "a method for producing a reduced slag treated material".
[0033] <Reducing slag>
[0034] In the steelmaking process, there are two methods of smelting steel using a blast furnace and a converter, and using an electric furnace. "Blast furnace slag" and "converter slag" are discharged from the former, and "electric furnace slag" is discharged from the latter.
[0035] In an electric furnace, iron waste (scrap iron) as the main raw material is heated and melted from the outside, and steel is produced through oxidation refining and reduction refining. The slag produced during oxidation refining is called "oxidation slag", and the slag produced during reduction refining is called "reduction slag". Oxidation slag and reduction slag are collectively called "electric furnace slag".
[0036] "Oxidized slag" is the slag produced when molten steel is stirred during the oxidation refining process. Oxidized slag contains about 30% iron oxide dissolved in metallic iron and slag, and is a hard slag with a relatively high density.
[0037] "Reducing slag" is the slag produced in the reducing refining process in which the oxidized slag is discharged after oxidative refining and slaked lime etc. are added to remove oxygen from the molten steel.
[0038] Reducing slag, like blast furnace slag, is a composition with CaO-SiO2-Al2O3-MgO as the main components. When the C2S contained in the reducing slag transforms from the α phase or β phase to the γ phase of low-temperature phase transition, since the density of the γ phase is lower than that of the α phase and β phase (the γ phase is low density), it will cause pulverization (sandification), making subsequent handling difficult (for example, slag with a basicity CaO / SiO2 weight ratio of about 1.5 times or more has the property of transforming from the α phase or β phase to the γ phase through the phase transition of 2CaO / SiO2 during its cooling process). Therefore, fluorine-based or boron-based slag pulverization inhibitors are usually added to inhibit the transformation from the α phase or β phase to the γ phase, so as to keep the block shape and be cooled.
[0039] Reaction 1
[0040]
[0041] For example, as shown in the above reaction formula 1, a phase transition to the γ phase occurs within the conversion temperature range of 675°C, the volume increases by about 1.12 times, the entire block expands and pulverizes, and it is a C2S material with very poor handling properties. In addition, in other words, the reduction slag discharged from the electric furnace is an environment where γC2S is easily obtained.
[0042] Generally, reduced slag (cooled while remaining in a lump form) discharged from an electric furnace is mixed with oxidized slag, and after unreacted components such as unreacted free lime (f-CaO) are hydrated and cured, it is used as a civil engineering material such as a roadbed material.
[0043] <γC2S>
[0044] "γC2S" is also called γ-type dicalcium silicate, which is a material with a chemical composition of γ-2CaO·SiO2. Figure 1 The composition of the crystalline region of "C2S" is shown in the ternary phase diagram of CaO-SiO2-Al2O3 (weight percentage of MgO = 10%).
[0045] γC2S is a carbon dioxide active material. Although it does not usually have hydration activity, it is a material with high utilization value as a concrete admixture. Specifically, after kneading γC2S with water, a small amount of cement and aggregate (fine / coarse) to make it into a mortar / concrete state, it can be brought into contact with high concentration (e.g. 5-20%) of carbon dioxide to obtain hardened mortar / concrete with normal strength in a short time (e.g. about five days). At this time, a large amount of carbon dioxide can be fixed in concrete.
[0046] γC2S is generally obtained by crushing limestone and silica, and then calcining the resulting material in a converter at 1200-1400°C. At this time, if the temperature is low, unreacted CaO will remain, and if the temperature is high, βC2S will be generated by high-temperature phase transformation. In particular, the more oxidizing the atmosphere, the more likely βC2S will remain.
[0047] In addition, limestone is used as the main raw material, and calcination requires a large amount of fossil fuels. Therefore, even if the conventional preparation method attempts to prepare γC2S as a material for fixing carbon dioxide, positive carbon is already produced when γC2S is produced.
[0048] Figure 3 The chemical composition (%) of γC2S is shown. When the chemical composition of γC2S is 100 weight %, the weight percentage of CaO is 65.1% and the weight percentage of SiO2 is 34.9%.
[0049] <Magnesium silicate>
[0050] Merwinite is a material with a chemical composition of 3CaO·MgO·2SiO2. Figure 1 The ternary phase diagram shown is the composition of the crystalline region of "magnesia calcite".
[0051] Like γC2S, magnesia calcium silicate is a carbon dioxide active material and has a high utilization value as a concrete admixture.
[0052] Figure 3 The chemical composition (%) of magnesia calcite is shown. When the chemical composition of magnesia calcite is 100% by weight, the weight percentage of CaO is 51.2%, the weight percentage of SiO2 is 36.6%, and the weight percentage of MgO is 12.2%.
[0053] <Reducing slag treatment materials>
[0054] The "reduced slag treated material" is a composition with γC2S and / or magnesia calcium silicate as the main components, and the main chemical components include CaO, SiO2, Al2O3, and MgO. In addition, it may further include chemical components derived from reduced slag, and may further include chemical components derived from additives or regulators (such as refining aids).
[0055] (chemical composition)
[0056] In the chemical composition of the reducing slag treatment material in which the total weight percentage of CaO, SiO2, Al2O3 and MgO is 100%, the weight percentage of CaO is 45-70%, preferably 50-70%, more preferably 50-65%, and further preferably 50-60%.
[0057] If the weight percentage of CaO is less than 45% (weight percentage less than 50%), it is much lower than the weight percentage of CaO contained in the effective component γC2S and magnesia-calcium mortar, so it is impossible to obtain a reduced slag treatment material containing high concentrations of γC2S and / or magnesia-calcium mortar as main components. In addition, if the weight percentage of CaO exceeds 70% (weight percentage exceeds 65%), it is much higher than the weight percentage of CaO contained in γC2S and magnesia-calcium mortar, so it is impossible to obtain the desired reduced slag treatment material.
[0058] In addition, in the above chemical composition, the weight percentage of SiO2 is 20-40%, preferably 25-40%, more preferably 25-35%, and further preferably 25-30%.
[0059] If the weight percentage of SiO2 is less than 20% (weight percentage less than 25%), it is much lower than the weight percentage of SiO2 contained in γC2S and magnesia-calcite, so the desired reduction slag treatment material cannot be obtained. In addition, if the weight percentage of SiO2 exceeds 40% (weight percentage exceeds 35%), it is much higher than the weight percentage of SiO2 contained in γC2S and magnesia-calcite, so the desired reduction slag treatment material cannot be obtained.
[0060] In addition, in the above chemical composition, the weight percentage of Al2O3 is 1-20%, preferably 1-15%, more preferably 5-15%, and further preferably 5-10%.
[0061] In addition, in the above chemical composition, the weight percentage of MgO is 1-20%, preferably 5-15%, and more preferably 5-10%.
[0062] That is to say, the preferred chemical composition of the reduced slag treatment material is that the weight percentage of CaO is 50-70%, the weight percentage of SiO2 is 25-40%, and the weight percentage of MgO is 5-15%, and the weight percentages of the components add up to 100%. More preferably, the weight percentage of CaO is 50-65%, the weight percentage of SiO2 is 25-35%, and the weight percentage of MgO is 5-10%.
[0063] If the chemical composition is as described above, a reduced slag treatment material can be obtained which has γC2S and / or magnesia calcium silicate as main components (main products) and has a high content of the main components.
[0064] At this time, by increasing the two components of SiO2 and Al2O3 to make it closer to (approximate) the chemical composition of γC2S and / or magnesia-calcium siliceous stone, a reduced slag treatment material with a high content of γC2S and magnesia-calcium siliceous stone can be obtained.
[0065] In addition, by increasing the SiO2 component to a larger amount than the Al2O3 component, a reduced slag treated material having a high content of γC2S and magnesia silicea can be obtained.
[0066] In addition, by increasing the MgO component relative to the Al2O3 component, a reduced slag treated material having a high magnesia-ladenite content can be obtained.
[0067] (Crystallized state)
[0068] The reduced slag treatment material is preferably Figure 1 The ternary phase diagram of CaO-SiO2-Al2O3 (MgO weight percentage = 10%) shows a composition of the crystal region of "C2S" or the crystal region of "magnesia calcite". More preferably, it is a composition of the primary crystal region of "C2S".
[0069] In this way, a reduced slag treated material having γC2S and / or magnesia calcium silicate as main components (main products) and having a high content of the main components can be obtained.
[0070] Here, the weight percentage of MgO is 10%, but it is not particularly limited. As mentioned above, the weight percentage of MgO is 1-20%, and preferably 5-15%.
[0071] In addition, the reduced slag treatment material does not necessarily have to be composed of the crystallized region of "C2S" or "magnesia calcite". Figure 1The ternary phase diagram shown may be a composition around the crystallization region of "C2S" or "magnesia calcite". Alternatively, the reduced slag treated material having the above chemical composition may be used regardless of the crystallization state. Even in this case, a reduced slag treated material having γC2S and / or magnesia calcite as the main component can be obtained.
[0072] <Particle size and particle size distribution>
[0073] It is preferred that the reduced slag treated material has an average particle size of 0.6 mm or less, more preferably an average particle size of 0.3 mm or less, and further preferably an average particle size of 0.105 mm or less. In addition, although the content of γC2S and / or magnesia silicea is slightly less, the reduced slag treated material may also have an average particle size of 1.2 mm or less.
[0074] The reason is that the low-temperature phase γC2S is a crystal with a lower density than the high-temperature phase-transformed C2S (α phase, β phase), and is characterized by being easy to pulverize and having a high content of fine powder (fine particles). In other words, since fine particles contain more effective components (γC2S and magnesia calcite), by recovering the reduced slag treated material with a smaller average particle size, a reduced slag treated material containing a high concentration of effective components can be obtained.
[0075] In addition, although there is no lower limit to the average particle size of the raw slag treatment material, for example, the reduced slag treatment material has an average particle size of 0.01 mm to 0.6 mm, preferably 0.02 mm to 0.6 mm, more preferably 0.02 mm to 0.3 mm. It may also have an average particle size of 0.044 mm to 0.6 mm.
[0076] For example, as shown in the following formula, the "average particle size" can be calculated from the weight ratio Rn (%) of particles in each particle size range and each median particle size Dn (mm) obtained in the particle size distribution measurement described later.
[0077] Average particle size = {Σ(Dn·Rn)} / 100
[0078] The particle size distribution of the reduced slag treated material is the value obtained when the reduced slag treated material is sieved (classified) using a JIS standard sieve (JIS Z8801-1: 2000) with a mesh size of 0.105-20 mm. If the mesh size is less than 0.105 mm, the value is the value obtained when the reduced slag treated material is sieved (classified) using a dry sieving device (jet sieve) with reduced pressure suction.
[0079] The details of a specific method for measuring the particle size distribution will be described in the examples described later.
[0080] It is preferred that the reduced slag treated material has an average particle size of 0.6 mm or less and has a particle size distribution such that when the reduced slag treated material is sieved using a JIS standard sieve, the reduced slag treated material can pass through a sieve having a mesh size of 0.6 mm.
[0081] More preferably, the reduced slag treated material has an average particle size of 0.3 mm or less and has a particle size distribution such that when the reduced slag treated material is sieved using a JIS standard sieve, the reduced slag treated material can pass through a sieve having a mesh size of 0.6 mm.
[0082] That is, it is preferable to obtain a reduced slag treated material in which slag particles of 0.6 mm or more (0.3 mm or more) are removed (removed as much as possible).
[0083] When sieving, it is preferred that the particle size distribution described below is obtained, and more than 70% of the total weight of the reduced slag treated material can pass through a sieve with a mesh size of 0.6 mm (0.3 mm). In addition, 100% of the total weight does not mean 100% purity.
[0084] In other words, the content of particles below 0.6 mm in the reduced slag treatment material is 70-100% by weight, preferably 80-100% by weight, more preferably 90-100% by weight, and further preferably 100% by weight.
[0085] Alternatively, the content of particles above 0.3mm and below 0.6mm in the reducing slag treatment material is 10-30% by weight, the content of particles below 0.3mm is 70-90% by weight, and the content of particles exceeding 0.6mm is below 5%, preferably 0%.
[0086] Alternatively, the content of particles above 0.105 mm and below 0.6 mm is 40-60% by weight, the content of particles below 0.105 mm is 40-60% by weight, and the content of particles exceeding 0.6 mm is below 5%, preferably 0%.
[0087] As described above, by appropriately setting the "chemical composition", "crystallization state", "average particle size" and "particle size distribution (particle content)", a reduced slag treated material containing a high concentration of γC2S and / or magnesia calcium silicate can be obtained.
[0088] <Concrete containing reduced slag treatment materials>
[0089] The "concrete containing a reduced slag treated material" is a concrete containing the above-mentioned reduced slag treated material and fixing carbon dioxide.
[0090] Specifically, water, cement, aggregate (fine / coarse) and reduced slag treated material as an admixture are kneaded into mortar / concrete, and then cured with high concentration (e.g. 5-20%) of carbon dioxide to obtain concrete containing reduced slag treated material.
[0091] A large amount of carbon dioxide is fixed in the concrete containing the reduced slag treated material. The greater the fixed amount of carbon dioxide is, the higher the compressive strength of the concrete is.
[0092] <Method for preparing reduced slag treated material>
[0093] The above-mentioned reduced slag processing material is prepared by at least the following steps: a "composition adjustment step" for adjusting the composition of the reduced slag discharged from the electric furnace, a "slow cooling step" for slowly cooling the reduced slag after the composition adjustment, and a "classification step" for classifying the slowly cooled reduced slag to obtain classified powder of the reduced slag.
[0094] The "ingredient adjustment step", "slow cooling step" and "classification step" performed in the preparation method are described in detail below. In addition, other steps can appropriately adopt known techniques.
[0095] In the "composition adjustment step", the chemical components of CaO, SiO2, Al2O3, and MgO of the reducing slag produced by the electric furnace are adjusted so that it has the chemical composition described above.
[0096] In detail, in order to suppress the increase of Al2O3 and MgO components, CaO and SiO2 are used as main components, and refining aids are added in the electric furnace to adjust the composition of the reduced slag. For example, Mn alloy, FeO or steelmaking slag can be cited as refining aids.
[0097] In addition to adding the above-mentioned refining aids, the chemical composition of the reduced slag can also be adjusted by other adjustment methods.
[0098] It is preferred that a reducing atmosphere be maintained in the electric furnace.
[0099] In addition, in the "composition adjustment step", the composition is adjusted so that it has a composition of "primary crystal region of C2S" in the ternary phase diagram of CaO-SiO2-Al2O3 (weight percentage of MgO = 10%).
[0100] To elaborate, it is known that the reduced slag produced by the electric furnace has Figure 1The chemical composition of the reduced slag is close to the primary crystallization region of "C2S" in the ternary phase diagram shown in FIG. Therefore, in order to make the chemical composition of the reduced slag close to the composition point of C2S (CaO: 65%, SiO2: 35%), raw materials such as slaked lime, dolomite and / or silica are added in the electric furnace to adjust the composition of the reduced slag. In this way, the composition of the reduced slag can be adjusted to be within the primary crystallization region of C2S.
[0101] In addition, it is necessary to supply MgO for the protection of the refractory material of the electric furnace. By supplying MgO, magnesia molteni can be obtained at the same time in addition to γC2S.
[0102] In the "slow cooling step", the reduced slag after the composition adjustment is slowly cooled in a reducing atmosphere in an electric furnace, and after being taken out of the electric furnace, it is slowly cooled in the range of 400-800°C at a temperature gradient of less than 20°C / min.
[0103] To explain in detail, in order to maintain the reducing atmosphere in the furnace, it is covered with rice husks to keep it insulated. Also, avoid blowing cold air or spraying water. In addition, other means besides the above can be used to maintain the reducing atmosphere.
[0104] By maintaining the reducing atmosphere in this way, metal ions such as iron are reduced to metals, and solid solution in the reducing slag can be suppressed, so that a reducing slag treated material having a high content of γC2S and / or magnesia ferrocene can be effectively obtained.
[0105] In addition, γC2S has a smaller solid solubility limit (solubility limit) of impurities than αC2S and βC2S. Therefore, by converting the C2S contained in the reduced slag into the γ phase state of low-temperature phase transformation, it is possible to further suppress its solid solution in the reduced slag, thereby obtaining a reduced slag treated material with fewer impurities.
[0106] In addition, in the "slow cooling process", heating or heat insulation operation is performed near the transformation temperature from β phase to γ phase (about 675°C), and by slowing down the temperature gradient, a reduced slag treated material with a high γC2S content can be obtained. If the cooling rate is too fast, the βC2S content will increase and the γC2S content will decrease.
[0107] Therefore, specifically, after being taken out from the electric furnace, it is slowly cooled with a mild temperature gradient within the range of 650-700°C, preferably within the range of 600-750°C, more preferably within the range of 600-800°C, further preferably within the range of 500-800°C, and further preferably within the range of 400-800°C.
[0108] In addition, within the above temperature range, slow cooling is performed with a temperature gradient of 30° C. / min or less, preferably 20° C. / min or less, more preferably 15° C. / min or less, and further preferably 10° C. / min or less.
[0109] In addition, in the "slow cooling step", a slag pulverization inhibitor that promotes the conversion of γC2S contained in the reduced slag after the component adjustment into αC2S and / or βC2S is not added.
[0110] In detail, in the past, in order to improve the handling properties of the reduced slag after cooling and to suppress the pulverization of the slag accompanying the transformation of C2S from the β phase to the γ phase, a slag pulverization inhibitor such as sodium borate was added. However, in the present embodiment, the purpose is to effectively obtain a reduced slag treated material with a high γC2S content. Therefore, it is preferred not to add a slag pulverization inhibitor but to slowly cool the reduced slag.
[0111] In addition, the slag pulverization inhibitor is not limited to sodium borate, and may be a fluorine-based or boron-based pulverization inhibitor, or other pulverization inhibitors, or the slag pulverization inhibitor may not be added. Alternatively, additives and regulators for preventing the conversion to γC2S may not be added.
[0112] In addition, in the "slow cooling step", the reduced slag after the composition adjustment is slowly cooled in the reducing atmosphere in the electric furnace, but it is not necessarily slowly cooled in the reducing atmosphere after being taken out of the electric furnace. That is, it can be slowly cooled in an oxidizing atmosphere outside the electric furnace.
[0113] Alternatively, conventional cooling may be performed in the electric furnace and slow cooling may be performed outside the electric furnace.
[0114] In the "classification step", the reduced slag after slow cooling is classified to obtain classified powder of the reduced slag.
[0115] In detail, the slowly cooled reducing slag agent is screened (classified) using a multi-stage sieve at room temperature to obtain a classified powder having a desired average particle size and particle size distribution. In addition, when screening with a sieve size of 0.105 mm or less, that is, when screening with a sieve size of 0.044 mm (45 μm) and 0.088 mm (90 μm), it is preferred to use a dry screening device (jet screen) with reduced pressure suction for screening.
[0116] For example, it is preferred to use a Ro-Tap type vibrating screening machine, and install various levels of JIS standard sieves with mesh sizes of 0.105mm (106μm), 0.15mm (150μm), 0.3mm (300μm), 0.6mm (600μm), 1.2mm (1.18mm), 2.4mm (2.36mm), 5mm (4.75mm), 10mm (9.5mm), and 20mm (19mm) in order from bottom to top according to the mesh size from small to large. The reduced slag treated material is put into the top sieve of the vibrating screening machine, vibrated for 10 minutes, and the desired classified powder can be obtained by recovering the remaining classified powder on each sieve. For example, a classified powder with an average particle size (particle size distribution) of less than 0.3mm or less than 0.6mm can be obtained.
[0117] In addition, various classification methods can be used in the classification process. For example, in addition to the screening method, an air flow classification method (gravity classification method, inertial classification method and centrifugal classification method) can be used.
[0118] As described above, through the "component adjustment process", "slow cooling process", "classification process" and other treatment processes, the reduced slag produced by the electric furnace can be used to prepare the reduced slag treated material with γC2S and / or magnesia calcium silicate as the main components.
[0119] In particular, according to the present preparation method, the reduced slag discharged from the electric furnace can be directly processed to obtain the reduced slag processed material.
[0120] Example
[0121] Hereinafter, an embodiment of the present invention will be described in detail. However, the present invention is not limited to the embodiment.
[0122] <Example: Reduction slag treatment material>
[0123] Based on the above-mentioned preparation method of the reduced slag treatment material, such as Figure 2 As shown in the figure, the reducing slag treated material is prepared by using the reducing slag discharged from the electric furnace under the conditions of (1) chemical composition, (2) crystal state, (3) cooling method, (4) whether to add a powdering prevention material, and (5) redox atmosphere. In addition, the reducing slag treated material is classified to obtain reducing slag treated materials with different average particle sizes.
[0124] Regarding (1) chemical composition, when the total weight percentage is 100%, the composition of the reduced slag is adjusted so that the weight percentage of CaO is 40-60%, the weight percentage of SiO2 is 20-30%, and the weight percentage of MgO is 5-10%.
[0125] Regarding (2) the crystal state, adjust to Figure 1The composition of the primary crystal region of C2S shown in the thick box in the ternary phase diagram shown.
[0126] Regarding the cooling method (3), the reduced slag is cooled by covering the furnace with rice husks to maintain the heat insulation state. In addition, no cold air is blown or water is sprayed. At this time, the reduced slag is slowly cooled in the range of 400-800°C with a temperature gradient of less than 20°C / min.
[0127] Regarding (4) whether or not to add a pulverization preventing material, no slag pulverization preventing agent (sodium borate) was added for suppressing pulverization accompanying the generation of γC2S.
[0128] Regarding (5) the redox atmosphere, the reduced slag is slowly cooled while maintaining the reducing atmosphere.
[0129] <Measurement Results of Particle Size Distribution>
[0130] Figure 2 : This is a graph showing the "measurement results of particle size distribution" of the reduced slag processed material obtained under the above conditions. In addition, the slag processed material with a particle size exceeding 20 mm was removed in advance.
[0131] The total weight of particles passing through a sieve with a mesh size of 1.2 mm (average particle size of 1.2 mm or less) is 61%. The total weight of particles passing through a sieve with a mesh size of 0.6 mm (average particle size of 0.6 mm or less) is 49%. The total weight of particles passing through a sieve with a mesh size of 0.105 mm (average particle size of 0.105 mm or less) is 22%. From the measurement results of "particle size distribution", it can be seen that there are relatively more fine powders.
[0132] <Chemical composition of reduced slag treatment materials, γC2S, and magnesia siliceous stone>
[0133] The reduced slag treated material obtained under the above conditions was classified to obtain reduced slag treated materials with different average particle sizes. Then, the "chemical composition" of the reduced slag treated material was measured. Similarly, the "chemical composition" of γC2S and magnesia ferrocene was measured.
[0134] When measuring the "chemical composition", the measurement was performed by the fundamental parameter method using a fluorescent X-ray analyzer (model: ZSXPrimusIV) manufactured by Rigaku Corporation.
[0135] Figure 3 It is a graph showing the results of "chemical composition (%)" of the reduced slag treated material before classification, the reduced slag treated materials with average particle sizes of less than 0.6 mm, less than 0.3 mm, more than 0.6 mm and less than 5.0 mm, γC2S and magnesia calcium silicate.
[0136] In addition, the reduced slag treated material with an average particle size of 0.6 mm or less was designated as "Example 1", the reduced slag treated material with an average particle size of 0.3 mm or less was designated as "Example 2", and the reduced slag treated material with an average particle size of more than 0.6 mm but less than 5.0 mm was designated as "Example 3". In addition, the reduced slag treated material before screening was designated as the "control group".
[0137] Reference Figure 3 From the measurement results, it can be seen that for "Example 1 (particle size less than 0.6 mm)", the content of CaO and SiO2 is higher than that of "Control Group (before screening)", which is close to the chemical composition of "γC2S" and "calcium magnesia stone".
[0138] In addition, regarding "Example 2 (particle size 0.3 mm or less)", the content of CaO and SiO2 is higher than that of "Example 1", and is closer to the chemical composition of "γC2S" and "calcite".
[0139] On the other hand, regarding "Example 3 (particle size 0.6-5.0 mm)", the content of CaO and SiO2 is lower than that of the "control group", and is far away from the chemical composition of "γC2S" and "calcium magnesia".
[0140] The above results show that the content of "γC2S" and "magnesia calcite" in the material with a particle size of less than 0.6 mm in the reduced slag treatment is higher (concentrated). In addition, the content of "γC2S" and "magnesia calcite" in the material with a particle size of less than 0.3 mm in the reduced slag treatment is further concentrated.
[0141] This result shows that "γC2S" is a low-density crystal in the phase transition process, which is easily pulverized and exists in large quantities in fine powder.
[0142] <Experiment for evaluating carbon dioxide fixation ability>
[0143] An experiment for evaluating the carbon dioxide fixation capacity (carbon dioxide content) was conducted using the reduced slag treated materials of Examples 1 to 3.
[0144] Specifically, the reduced slag treatment material of each embodiment was crushed and adjusted using a mortar so that the crushed slag particles were less than 0.3 mm. Then, 5.0 g of the reduced slag treatment material and 2.5 g of water (tap water) were placed in a polystyrene plastic bottle (bottle body diameter 30 mm) and mixed with a spatula. Then, it was placed in a curing tank with a temperature of 40°C, a relative humidity of 60%, and a carbon dioxide concentration of 20%, and 2.5 g of water was added every day for a certain period of wet air curing.
[0145] After 1 day, 3 days and 5 days of curing (carbonization curing), the samples were taken out, coarsely crushed and dried at 105°C for 24 hours. After drying, the samples were crushed and the carbon dioxide fixation capacity (%) was measured by coulometric method. As a reference value, the carbon dioxide fixation capacity (%) when using γC2S was also measured.
[0146] <Coulomb method>
[0147] Hydrochloric acid was added to the sample placed in the conical flask, stirred with a stirrer, and the generated carbon dioxide gas was introduced into the absorption liquid in the coulometer (made by Japan Ans Co., Ltd., model 2000S-CAT) by nitrogen gas. The carbon amount was measured based on the amount of electricity flowing to the electrode to keep the absorption liquid in a neutral state, and converted into carbon dioxide fixation capacity (%) using the following formula.
[0148] CO2={(AB)×3.664÷S}÷10000
[0149] CO2: CO2 fixation capacity (%) ※Also called CO2 content
[0150] A: Carbon content of the measured sample (μg)
[0151] B: Carbon content when measuring an empty conical flask (μg)
[0152] S: Sample size (g)
[0153] Furthermore, more specifically, samples were prepared with reference to Non-Patent Document 1, and the carbon dioxide fixation capacity (%) was measured by the coulometric method.
[0154] Figure 4 The evaluation results of the carbon dioxide fixation capacity (%) of the reduced slag-treated materials and γC2S of Examples 1-3 are summarized.
[0155] from Figure 4 The evaluation results show that "Example 1 (particle size 0.6 mm or less)" and "Example 2 (particle size 0.3 mm or less)" show higher carbon dioxide fixation capacity (%) than "Example 3 (particle size 0.6-5.0 mm)".
[0156] In addition, "Example 2 (particle size 0.3 mm or less)" showed a higher carbon dioxide fixation capacity (%) than "Example 1 (particle size 0.6 mm or less)".
[0157] These results show that the reduced slag treated material with a smaller average particle size (finer powder) is closer to the value of carbon dioxide fixation capacity of "γC2S". In addition, this also shows that it contains a higher concentration of "γC2S".
[0158] from Figure 4The evaluation results show that when the carbon dioxide fixation capacity of "γC2S" is set to 100, the carbon dioxide fixation capacity value of "Example 1" is 75-77 (Day 1: 76.9, Day 3: 76.2, Day 7: 75.0). In addition, the carbon dioxide fixation capacity value of "Example 2" is 83-93 (Day 1: 92.3, Day 3: 85.7, Day 7: 83.3).
[0159] That is, the reduced slag treated material of the example exhibited a stable carbon dioxide fixation capability similar to that of "γC2S". In addition, the reduced slag treated material with a smaller average particle size (finer powder) was closer to the value of carbon dioxide fixation capability of "γC2S".
[0160] The above shows that, regarding the preparation method of the above-mentioned reducing slag treatment material, by optimizing the "chemical composition", "crystallization state", "cooling method", "whether to add anti-powdering material", and "oxidation-reduction atmosphere", the "average particle size" and "particle size distribution (particle content)" are optimized, and it is possible to effectively prepare a reducing slag treatment material containing a high concentration of γC2S and / or magnesia calcium silicate.
Claims
1. A reducing slag treatment material, which is a reducing slag treatment material with γC2S and / or magnesia calcium silicate (3CaO·MgO·2SiO2) as main components, characterized in that: The reduced slag treatment material has an average particle size of less than 0.6 mm; And has the following particle size distribution, when the reduced slag treated material is sieved using a JIS standard sieve (JIS Z8801-1:2000), more than 80% of the total weight of the reduced slag treated material can pass through a sieve with a mesh size of 0.6 mm.
2. The reduced slag treatment material according to claim 1, characterized in that: When the chemical composition of the reduced slag treatment material is 100% by weight, the weight percentage of CaO is 50-70%, the weight percentage of SiO2 is 25-40%, and the weight percentage of MgO is 5-15%; The reduced slag treatment material has a particle size distribution in which more than 90% of the total weight can pass through a sieve with a mesh size of 0.6 mm.
3. The reduced slag treatment material according to claim 1, characterized in that: The reduced slag treatment material has an average particle size of less than 0.3 mm; And has the following particle size distribution, when the reduced slag treated material is sieved using a JIS standard sieve, more than 80% of the total weight of the reduced slag treated material can pass through a sieve with a mesh size of 0.3 mm.
4. The reduced slag treatment material according to claim 1, characterized in that: When the chemical composition of the reduced slag treatment material is 100% by weight, the weight percentage of CaO is 50-65%, the weight percentage of SiO2 is 25-35%, the weight percentage of MgO is 5-10%, and the chemical composition of the primary crystallization region of C2S in the CaO-SiO2-Al2O3 (weight percentage of MgO=10%) ternary phase diagram; The reduced slag treatment material has a particle size distribution in which more than 90% of the total weight of the reduced slag treatment material can pass through a sieve with a mesh size of 0.3 mm.
5. A concrete containing reduced slag treated material, characterized in that: A reduced slag treatment material according to claim 1 is contained and carbon dioxide is fixed.
6. A method for preparing a reduced slag treatment material, which is a method for preparing a reduced slag treatment material with γC2S (γ-2CaO·SiO2) and / or magnesia calcite (3CaO·MgO·2SiO2) as main components by using reduced slag discharged from an electric furnace, characterized in that: It includes ingredient adjustment process, slow cooling process and classification process; The composition adjustment step adjusts the composition of the reduced slag; The slow cooling step slowly cools the reduced slag after the composition is adjusted; The classification step is to classify the slowly cooled reduced slag to obtain classified powder of the reduced slag; In the classification process, the classified powder is obtained, having an average particle size of 0.6 mm or less and a particle size distribution such that more than 80% of the total weight can pass through a sieve with a mesh size of 0.6 mm when sieved using a JIS standard sieve (JIS Z8801-1:2000).
7. The method for preparing the reduced slag treated material according to claim 6, characterized in that: In the composition adjustment step, the composition of the reduced slag is adjusted so that the composition is in the primary crystal region of C2S in the ternary phase diagram of CaO-SiO2-Al2O3 (weight percentage of MgO=10%); In the slow cooling step, the reduced slag after the composition adjustment is slowly cooled in a reducing atmosphere; In the classification process, the classified powder is obtained, having an average particle size of 0.3 mm or less and a particle size distribution such that when sieved using a JIS standard sieve, more than 80% of the total weight can pass through a sieve with a mesh size of 0.3 mm.
Citation Information
Patent Citations
Concrete kneading material, co2 absorption precast concrete and method of producing the same
JP2011168436A